Biochar type and ratio as a peat additive/partial peat replacement in growing media for cabbage seedling production - Chrysargyris, Antonios; Prasad, Munoo; Kavanagh, Anna; Tzortzakis, Nikos G. (My University, 2019)
© 2019 by the authors. Biochar has been proposed mainly as a soil amendment, positively affecting plant growth/yield, and to a lesser degree for growing media. In this study, four commercial grade biochars (A-forest wood; B-husks and paper fiber; C-bamboo and D-fresh wood screening), mostly wood-based materials, were selected. Initial mixtures of peat (P) with different Biochar type and ratios (0-5-10-15-20%) were selected for cabbage seedling production. Biochar material had high K content and pH ≥ 8.64 which resulted in increased pH of the growing media. Biochar A and C at 20% reduced cabbage seed emergence. Biochar A, B and D maintained or improved plant growth at low ratio (i.e., 5–10%) while all Biochars increased N, K and P content in leaves. Biochars A and D were further examined at 7.5% and 15% with the addition of two doses of minerals (1-fold and 1.5-fold). Biochar A and D, initially stimulated seed emergence when compared to the control. High dose of fertilizer favored plant growth in Biochar A at 7.5% and Biochar D at 15%. Leaf stomatal conductance was decreased at Biochar A+Fert at 7.5% and Chlorophyll b content was decreased at Biochar A+Fert at 15%. The presence of Biochar A increased the antioxidant activity (as assayed by 2,2-diphenyl-1-picrylhydrazyl-DPPH). Lipid peroxidation was higher in plants grown with fertilized peat and Biochar A at 15%, activating antioxidant enzymatic metabolisms. Potassium, phosphorous and copper accumulation and magnesium deficiency in cabbage leaves were related to the Biochar presence. Wooden biochar of beech, spruce and pine species (Biochar A) at 7.5% and fertilized biochar of fruit trees and hedges (Biochar D) were more promising for peat replacement for cabbage seedling production.
Keywords: Biochar; Brassica; Cabbage; Emergence; Growth; Peat